Account in The Devil All the Time Movie Script - Gerry Shabirtz; Fina Amalia Masri; Neil Amstrong (English Literature Study Program, Faculty of Humanities, Universitas Halu Oleo, 2022)
This research aims to discuss Account in The Devil All the Time movie script, based on Scott and Layman's theory on the Justification and excuses aspects. Data was collected through searching, downloading, reading, watching, and coding, and the data collected was analyzed through several steps; presenting, describing, interpreting, classifying, and concluding the results of this research. The results showed that the account exists and is applied by the character. The researcher finds several types of accounts, namely justification 5, defeasibility 3, scapegoating 3, and biological 2. One type of account was not found, namely an accident. In the finding, the researcher finds that every excuse contains justification but every justification does not contain an excuse. Moreover, the justification aspect is more dominantly used because the character always justifies the bad behavior of others or themselves. In excuses, the defeasibility aspect is used because many murders are committed based on victims who deserve to be killed. The scapegoating aspect is used by the character to accuse others of the mistakes he made so as not to become a suspect of his actions and the biological is the last factor that causes Account's behavior in this movie script.